Treatment of Invasive Cervical Resorption in a Central Incisor by Intentional Replantation: A Case Report - Ricardo Gomes de Calda Nogueira Filho, Luiz; Henrique de Freitas Fernandes, Pedro; Ricardo Gomes de Caldas Nogueira, Luiz; Tavares Velozo Telles, Christianne; Maria Coelho Travassos, Rosana; Santana de Albuquerque, Diana (Iranian Endodontic Journal, 2024)
Invasive cervical resorption (ICR) is an aggressive pathological condition that can affect any permanent tooth. This process is characterized by replacement of the tooth structure with granulomatous fibrovascular or fibro-osseous tissue. Despite its asymptomatic nature, ICR can lead to tooth loss. This study reports a case of ICR in a 15-year-old boy with a history of dental trauma. The patient had a diagnosis of ICR in tooth #21. After considering the risks of an external surgical approach and exclusive endodontic treatment, intentional re-implantation combined with extraoral composite resin restoration and endodontic treatment was proposed. The procedure consisted of atraumatic tooth extraction, removal of granulomatous tissue, restoration of the cavity with composite resin, re-implantation of the tooth in the alveolus, and endodontic treatment. This approach resulted in satisfactory repair of the resorptive lesion observed in over 3 years of follow-up. This case highlights intentional re-implantation combined with appropriate endodontic treatment as a viable treatment option for ICR.